Two Sisters and a Piano and Other Plays. - Cruz, Nilo (Theatre Communications Group, 2005)
Nilo Cruz is the most produced Cuban American playwright in the United States and was the first dramatist of Hispanic descent to receive the Pulitzer Prize. In his plays, Cruz almost always journeys back to Cuba, even when the play is not set there. Cruz is a sensualist, a conjurer of mysterious voyages and luxuriant landscapes. He is a poetic chronicler, a documentarian of the presence of Latin people in American life. He conveys the strength and persistence of the Cuban spirit through a wholly dramatic imagination. This volume also includes the oneact play, Capriccio.